Práticas pedagógicas dos professores de educação física frente a inclusão de alunos com deficiência - Mahl, Eliane (2012)
Currently there are a lot of national and international social-educative politics aiming to assure an efficient application of equal opportunities for people with special needs. The assurance of access and permanence spreads over all segments and subject areas, such as Physical Education and, for being a mandatory part of primary education and comprising the pedagogical proposition, it cannot be indifferent to the inclusive education movement. Considering that pedagogical practices that are planned, organized and targeted indistinctly to all students are of fundamental importance to good quality education, this study aims at investigate the concepts and actions that guide the pedagogical practices related to the inclusion of students with special needs of physical education teachers from the public schools of a city of São Paulo State, comparing these practices with their speech. In this way, it is a qualitative study outlined by the transversal descriptive model since it analyzes or situates a group of people into a variable or concept, providing its description. I n order to achieve the study s goal one used two artifacts: field diaries for registering what was observed on the physical education teachers pedagogical practices, and semi-structured interviews, and it was chosen to apply content analysis. Therefore, the methodological path that was followed allowed one to envision different nuances of the pedagogical practices applied by some teachers, such as: a) lack of commitment to the area, the students education, continued education, the discussion that involves the education system and the difficulties inherent to the teaching duty; b) lack of knowledge about the legal regulation of the inclusion process; c) disenchantment with the profession and, most importantly, disparity and distancing of their pedagogical practices against the inclusion of students with special needs and the inclusion speech. However, there is a light on the horizon: some teachers surprisingly kept pedagogical practices meeting the standards that construct an education system which is, in this case related to Physical Education, more human, more serious, more experienced, more successful and more inclusive. Where, in the light of inclusion and by means of human rights, respect to diversity presupposes tolerance to the peculiarities of each student/person, consolidating in practice the so heated speeches despite of inclusion. In these meanders, one believes studying the inclusion process by observing the physical education teachers pedagogical practices and speeches allowed to comprehend the actual situation of public schools and their inclusion possibilities, where the knowledge needed for inclusive education is set, but the big challenge is the doubts and insecurity the teachers have about that process, besides the possibility (or impossibility?) of using all the developed resources in order to provide quality education and foster inclusive education. In view of the problem shown, one believes it is extremely important that every teacher regardless of subject area improves her knowledge about inclusion of students with special needs even though there are not yet students with such condition in the schools she works. After all, inclusion of students with special needs is not an option anymore but a guaranteed right and yet it is as indispensable as obvious to have consistence between speech and inclusive practice, for it is worthless addressing a speech and not doing what it states.